Mortality in Perinatally HIV-infected Adolescents After Transition to Adult Care in Spain - Berzosa Sánchez, Arantxa; Jiménez De Ory, Santiago; Frick, M Antoinette; Menasalvas Ruiz, Ana Isabel; Couceiro, José Antonio; Mellado, Mª José; Bisbal, Otilia; Albendin Iglesias, Helena; Montero, Marta; Roca, Cristina; Samperiz, Gloria; Cervero, Miguel; et al. (Wolters Kluwer, 2021)
Introduction: After the introduction of combination antiretroviral treatment, (ART) mortality in HIV-infected patients has dramatically decreased. However, it is still high in patients at risk, as adolescents transitioning to adult care (AC) without virologic control. The aim of this study was to characterize mortality and comorbidities of perinatally infected HIV (PHIV) patients after transition to AC. Methods: A multicenter retrospective study from patients included in the CoRISpe-FARO Spanish cohort was conducted. PHIV patients who died after transition to AC between 2009 and 2019 were included. Clinical, immunovirologic characteristics, treatments received, comorbidities and causes of death were described. Results: Among 401 PHIV patients, 14 died (3.5%). All were Spanish, 11/14 (78.6%) women. The median age at diagnosis was 1.5 years (interquartile range [IQR] 0.5-3.9), at transfer to AC was 18 years [16.1-19.9] and at death was 25.8 years [23.6-27.1]. In pediatric units [pediatric care (PC)], CD4+ nadir was 85 cells/¿L [IQR 9.7-248.5] and 6/14 patients were classified as C-clinical stage. During AC, all patients were on C-clinical stage and CD4+ nadir dropped to 11.5 cells/¿L [4.5-43.3]. cART adherence was extremely poor: in PC, 8/14 patients registered voluntary treatment interruptions; only one had undetectable VL at transition. In AC, 12/14 patients stopped treatment 2 or more periods of time. All deaths were related to advanced HIV disease. Mental health disorders were observed in 7/14 (50%). Main complications described: recurrent bacterial infections (57.1%), wasting syndrome (42.9%), esophageal candidiasis (28.6%) and Pneumocystis jirovecii pneumonia (28.6%). Four women had 11 pregnancies; 5 children were born (none infected). Conclusions: Young adults PHIV infected who transition to AC without virologic suppression or proven ability to adhere to ART are at high risk of mortality. Mortality was noted as a consequence of advanced HIV disease, frequent mental health problems and poor adherence to ART.